Transposições ortográficas e estrutura da sílaba na escrita infantil - Coelho, Bianca de Carvalho [UNESP] (2016)
OBJECTIVES: The general objective of this paper was to investigate the transpositions of grapheme in their conventional positions in children´s writing from the 1st to the 4th grade of Elementary School in relation to the Brazilian Portuguese words registration (BP) as well as the possible relationship of these shifts with phonetic-phonological aspects of the language. Its specific objectives were: (1) verify the types of transpositions according to their occurrence within the same syllable in the word (intrassyllables) and in different syllables (intersyllables); (2) verify the phonological structure of syllables in the occurrence of transpositions; (3) verify the direction of transpositions regarding the syllabic position; (4) verify the phonological class of the corresponding phoneme to the transposed grapheme; (5) verify the relationship of lexical stress with the occurrence of transpositions; (6) verify possible relations between the transposition and the initial syllable of the word; (7) verify possible transformations of different school grades transpositions. METHODS: We analyzed 2972 children´s textual productions, from 2001 to 2004, who attended from the 1st to the 4th grades of Elementary School, in public schools in the city of São José do Rio Preto. In these productions were found 135 transposition events, such occurrences were categorized according to each objective. RESULTS: In relation to each one of the research specific objectives, the results showed the following trends: (1) no significant difference between intrassyllable and intersyllable occurrences; (2) predominance of syllabic structure CVC and CV in transpositions; (3) predominance of grapheme occupying the simple coda in transpositions; (4) predominance of phonological class of vibrant consonants in transpositions; (5) no statistical difference between transpositions involved in unstressed syllables and stressed syllables; (6) greater presence of transpositions toward (or in) the first syllable of the word; and (7) predominance of transpositions in the first two years of the first school year. CONCLUSION: the trends shown by the results allow us to affirm that the spelling transpositions do not occur randomly, but rather motivated by linguistic factors. They also allow us to declare that, in addition to the school having a strong role in the acquisition of writing, the inclusion of children in literacy practices more detailed to the spelling, is a factor that works positively in favor of this decreasing.